2020
DOI: 10.25100/cdea.v36i67.8744
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Mobile Banking by Microentrepreneurs at the Bottom of the Pyramid

Abstract: The use of mobile phones has increased globally, offering developing countries the opportunity to improve financial inclusion through mobile banking. However, mobile banking has been little adopted by microentrepreneurs at the bottom of the pyramid, and studies that explain this phenomenon is incipient. Therefore, this study aims to establish factors that influence mobile banking adoption by microentrepreneurs, from the Theory of Planned Behavior (TPB), extended to the relative advantage and perceived risk. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Trust in technology: This research determines a strong relationship between trust in technology and mobile financial services. Significantly, these findings are consistent with prior research (Benamati and Serva, 2007;Kibicho and Mungai, 2019;Msweli and Mawela, 2021;Ruano-Arcos et al, 2020;Salemink et al, 2017) that considers trust as one of the most important predictors of mobile banking adoption. Moreover, the lack of trust in technology is a factor impacting the adoption of mobile banking.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Trust in technology: This research determines a strong relationship between trust in technology and mobile financial services. Significantly, these findings are consistent with prior research (Benamati and Serva, 2007;Kibicho and Mungai, 2019;Msweli and Mawela, 2021;Ruano-Arcos et al, 2020;Salemink et al, 2017) that considers trust as one of the most important predictors of mobile banking adoption. Moreover, the lack of trust in technology is a factor impacting the adoption of mobile banking.…”
Section: Discussionsupporting
confidence: 91%
“…In Colombia, research has been conducted on mobile banking adoption in various contexts such as services for microentrepreneurs in vulnerable conditions, where trust and attitude are two common factors enabling the adoption of digital services (Ruano-Arcos et al, 2020). Another study highlighted perceived trust and security as the factors influencing the acceptance and use of mobile banking in Colombia (Giraldo et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that digital financial services, excluding certain low-penetration variables, contribute significantly to financial inclusion (Fernandes et al, 2020). Moreover, the use of mobile phones globally has provided developing countries with the opportunity to improve financial inclusion through mobile banking, thereby benefiting microentrepreneurs at the bottom of the pyramid (Ruano-Arcos et al, 2020). In the context of financial inclusion, the role of blockchain technology and cryptocurrencies has garnered attention.…”
Section: Key Technologies Driving Financial Inclusionmentioning
confidence: 99%
“…Furthermore, they also foster mobile banking usage by agreeing that they would recommend it to other people (M = 4.34). Equally, the study of Ruano-Arcos et al (2020) The respondents' behavior towards comfort using AI mobile banking services is presented in Table 9. The results show that it gathered the lowest composite mean (M = 3.62).…”
Section: Descriptive Statisticsmentioning
confidence: 99%